2020
DOI: 10.1186/s13756-020-0689-x
|View full text |Cite
|
Sign up to set email alerts
|

The appropriateness of antimicrobial use in the outpatient clinics of three hospitals in the Netherlands

Abstract: Objectives: Antimicrobial Stewardship Programs commonly have an in-hospital focus. Little is known about the quality of antimicrobial use in hospital outpatient clinics. We investigated the extent and appropriateness of antimicrobial prescriptions in the outpatient clinics of three hospitals. Methods: From June 2018 to January 2019, we performed ten point prevalence surveys in outpatient clinics of one university hospital and two large teaching hospitals. All prophylactic and therapeutic prescriptions were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
(44 reference statements)
1
4
1
3
Order By: Relevance
“…However, since the criteria for the appropriate use assessment varied among individual studies, only a general comparison can be generated between study data. In brief, the percentage of appropriate antibiotic prescriptions in this study was higher than in previous studies in the country [16,28], and also higher than in some countries around the world [10][11][12]29,32,33]. However, in our sample population, there were a few elderly (20.2%) and children (1.9%) who received the antibiotics; this also means that vulnerability and multi-morbidity are less likely to affect decision-making on antibiotic prescribing of doctors and might be a supporting reason for the lower rate of inappropriate usage.…”
Section: Appropriate Usage Of Antibioticscontrasting
confidence: 71%
See 1 more Smart Citation
“…However, since the criteria for the appropriate use assessment varied among individual studies, only a general comparison can be generated between study data. In brief, the percentage of appropriate antibiotic prescriptions in this study was higher than in previous studies in the country [16,28], and also higher than in some countries around the world [10][11][12]29,32,33]. However, in our sample population, there were a few elderly (20.2%) and children (1.9%) who received the antibiotics; this also means that vulnerability and multi-morbidity are less likely to affect decision-making on antibiotic prescribing of doctors and might be a supporting reason for the lower rate of inappropriate usage.…”
Section: Appropriate Usage Of Antibioticscontrasting
confidence: 71%
“…The inappropriate rate at an emergency department in Australia was reported with 32.7% throughout 2016 [32]. In the Netherlands, a recent study on antimicrobial use in the outpatient clinics showed that among 95% of prescriptions for which a guideline was present, the guideline non-adherence rate was 25.6% in term of antimicrobial agent, dose and duration [33]. However, since the criteria for the appropriate use assessment varied among individual studies, only a general comparison can be generated between study data.…”
Section: Appropriate Usage Of Antibioticsmentioning
confidence: 99%
“…In other studies, the highest rates of unnecessary prescribing have been noted for acute bronchitis, acute sinusitis, and viral upper respiratory infections, 6,13,23 where azithromycin, fluoroquinolones, and amoxicillin-clavulanate comprise a majority of the inappropriate antibiotic prescriptions. 7,8 Consistent with these studies, azithromycin was the most prescribed antibiotic in our population as well. Before the intervention, the geriatric clinic had higher use of narrower-spectrum antibiotics, particularly doxycycline, compared to previous studies 5,6 ; however, the intervention was able to limit the duration of antibiotics for those already prescribed the appropriate agent.…”
Section: Discussionsupporting
confidence: 86%
“…Prior large-scale studies have repeatedly demonstrated that antibiotics are overprescribed for outpatient acute respiratory conditions, 5,6 and the rate of inappropriate prescriptions ranges from 35% to 76% based on the specific condition. [6][7][8] Not only do inappropriate antibiotic prescriptions contribute to an increase in antimicrobial resistance, but antibiotics are also associated with serious adverse effects such as drug-drug interactions, allergic reactions, neurologic or psychiatric effects, and Clostridiodes difficile infection. 9 According to the US Centers for Disease Control and Prevention (CDC), there are 223,900 cases of C. difficile infection and >12,800 deaths yearly.…”
mentioning
confidence: 99%
“…Such finding was congruently highlighted in a study conducted by van den Broek et al where antibiotics accounted for 79% of prescriptions. 38 Narrow-spectrum antibiotics were more frequently prescribed compared with broad-spectrum antibiotics. This finding is consistent with recommendations of treating childhood infections using narrow-spectrum antibiotics, as such an approach would essentially improve treatment outcomes and control antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 99%